Survival and risk perceptions of healthcare professionals and patients - Carina Ferreira; Teresa Abreu; Ricardo Gonçalves; José M. Pereira; Mário Basto (Universitas Airlangga, 2023)
In order to make an informed, evidence-based decision, it is vital to recognize numbers, statistics and concepts that are apparently transparent but are not always adequately accounted for. Health professionals, patients, and others frequently misinterpret numbers, statistics and concepts in healthcare. Among the many repercussions of health literacy, appropriate decision-making and the reduction in the number of interventions and treatments stand out, resulting in an improvement in people's health and a decrease in overtreatment and health expenses. This study intends to evaluate how properly health professionals and the public, in general, comprehend and interpret some health-related numbers. To accomplish this goal, the researchers shared a questionnaire made available online in Portugal from January 2, 2019, until April 12, 2019. The final sample comprised 485 respondents; 154 physicians, 142 nurses, and 189 people from other professions. The findings suggest that there is a problem with widespread numerical illiteracy, which should not be the case, highlighting the need to improve the numerical and statistical health literacy of both health professionals and the general population. So, medical professionals and patients must thus comprehend the statistics and health-related concepts to obtain the proper consent.